Trace mercury migration and human exposure in typical mercury-emission areas by compound-specific stable isotope analysis. (April 2023) - Wang, Bo; Yang, Shaochen; Li, Ping; Qin, Chongyang; Wang, Chuan; Ali, Muhammad Ubaid; Yin, Runsheng; Maurice, Laurence; Point, David; Sonke, Jeroen E.; Zhang, Leiming; Feng, Xinbin
Highlights: Human methylmercury (MeHg) exposure pathways were quantified by stable isotope in typical Hg-emission areas. CSIA can track pollution sources of MeHg and inorganic Hg (IHg) in rice grain. Fish MeHg potentially originates from plankton in the euphotic zone. Fish IHg was partially derived from in vivo demethylation of MeHg. Positive shifts of δ 202 Hg from diet to hair indicated internal MeHg demethylation. Abstract: Anthropogenic mercury (Hg) emissions have increased significantly since the Industrial Revolution, resulting in severe health impacts to humans. The consumptions of fish and rice were primary human methylmercury (MeHg) exposure pathways in Asia. However, the lifecycle from anthropogenic Hg emissions to human MeHg exposure is not fully understood. In this study, a recently developed approach, termed MeHg Compound-Specific Isotope Analysis (CSIA), was employed to track lifecycle of Hg in four typical Hg-emission areas. Distinct Δ 199 Hg of MeHg and inorganic Hg (IHg) were observed among rice, fish and hair. The Δ 199 Hg of MeHg averaged at 0.07 ± 0.15 ‰, 0.80 ± 0.55 ‰ and 0.43 ± 0.29 ‰ in rice, fish and hair, respectively, while those of IHg averaged at − 0.08 ± 0.24 ‰, 0.85 ± 0.43 ‰ and − 0.28 ± 0.68 ‰. In paddy ecosystem, Δ 199 Hg of MeHg in rice showed slightly positive shifts (∼0.2 ‰) from those of IHg, and comparable Δ 199 Hg of IHg between rice grain and raw/processed materials (coal, Hg ore, gold ore and sphalerite) were observed. Simultaneously, it was proved that IHg in fish muscle was partially derived from in vivo demethylation of MeHg. By a binary model, we estimated the relative contributions of rice consumption to human MeHg exposure to be 84 ± 14 %, 58 ± 26 %, 52 ± 20 % and 34 ± 15 % on average in Hg mining area, gold mining area, zinc smelting area and coal-fired power plant area, respectively, and positive shifts of δ 202 HgMeHg from fish/rice to human hair occurred during human metabolic processes. Therefore, the CSIA approach can be an effective tool for tracking Hg biogeochemical cycle and human exposure, from which new scientific knowledge can be generated to support Hg pollution control policies and to protect human health.